Penerapan Hukum Kamma Dalam Meningkatkan Moralitas Remaja Dikehidupan Bermasyarakat - Tedi Willia Nando; Alta Defano Gautama; Jefri Mauruntu (Jounal Nyanadassana, 2023)
This journal explores the use of literature-based research techniques to examine how the law of kamma can be used to increase adolescent morality in communal life. The purpose of this research is to determine how the Buddhist notion of kamma law can be used to increase the morality of youth in their social interactions. This research method involved gathering information from primary and secondary sources relating to the ideas of the law of kamma and youth morality. The findings show that through increasing positive values, avoiding negative values, and developing strong and enduring characters, the idea of the law of kamma can be applied to increase the morality of youth. Research shows that using the notion of the law of kamma can be a useful substitute for increasing youth morality in communal life.